(untitled) (Medicine Today, 2019)
Introduction: Compared with a fetus with cephalic presentation, a breech fetus faces increased risk during labour and delivery of asphyxia from cord compression and of traumatic injury during delivery of the shoulders and head. Caesarean section avoids most of this risk. The purpose of this study was to evaluate the feasibility of vaginal delivery of uncomplicated singleton breech presentation by evaluating early neonatal morbidity and mortality as well as maternal morbidity following vaginal and caesarean delivery for breech presentation. Materials and Methods: This is a cross sectional comparative study.104 women with singleton breech presentation at term in labour were included consequetively in labour ward of Institute of Child and Mother Health (ICMH). Informed consent was taken from them. Neonatal and maternal outcome were recorded and statistical analysis was done using SPSS version 22. Results: APGAR at 5 min and Neonatal Intensive Care Unite (NICU) admission were not affected by mode of delivery. Long term neonatal outcome is similar in either mode of delivery. Maternal morbidity and duration of hospital stay is increased in caesarean births. Conclusion: Neonatal outcome did not depend on mode of delivery though maternal morbidity and cost of care is increased following Caesarean Section. Proper selection of cases and by improving skill & confidence in new generation obstetrician, vaginal delivery of singleton fetuses in breech presentation at term remains a safe option that can be offered to a woman in a tertiary care centre. Medicine Today 2019 Vol.31(1): 23-26